2021
DOI: 10.1111/ejn.15539
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion imaging of fornix and interconnected limbic deep grey matter is linked to cognitive impairment in multiple sclerosis

Abstract: Diffusion tensor imaging (DTI) and volumetric magnetic resonance imaging (MRI) have shown white matter (WM) and deep grey matter (GM) abnormalities in the limbic system of multiple sclerosis (MS) participants. Structures like the fornix have been associated with cognitive impairment (CI) in MS, but the diffusion metrics are often biased by partial volume effects from cerebrospinal fluid (CSF) due to its small bundle size and intraventricular location. These errors in DTI parameter estimation worsen with atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…Third, left and right hippocampal metrics were averaged together to minimize the already large number of comparisons. Separate left and right analyses showed similar findings (data not shown) and most previous studies have shown similar left and right atrophy in MS 13,16,18 or have analyzed left and right metrics together, 10,11,15,17,20 including DTI studies 25–27,60 . Fourth, MRI metrics such as MD and T2 are sensitive to increased water content, which could occur from partial volume effects with CSF and be exacerbated as a result of greater atrophy, even at this improved high resolution.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Third, left and right hippocampal metrics were averaged together to minimize the already large number of comparisons. Separate left and right analyses showed similar findings (data not shown) and most previous studies have shown similar left and right atrophy in MS 13,16,18 or have analyzed left and right metrics together, 10,11,15,17,20 including DTI studies 25–27,60 . Fourth, MRI metrics such as MD and T2 are sensitive to increased water content, which could occur from partial volume effects with CSF and be exacerbated as a result of greater atrophy, even at this improved high resolution.…”
Section: Discussionsupporting
confidence: 70%
“…Neuronal degeneration caused by axonal transection due to lesions in the fornix, which is the major efferent WM pathway from the hippocampus, could also trigger diffuse neuronal loss in the hippocampus that could happen anywhere along the anterior posterior long axis of the hippocampus. A previous CSF suppressed DTI study in the same MS cohort reported marked fornix atrophy (~26%) and microstructural diffusion abnormalities (6%–12%) in MS that were greater in the CI group 25 . As the extent of fornix atrophy and diffusion abnormalities are greater than hippocampus atrophy, diffusion, and T2 relaxometry differences when compared with controls in this MS cohort, we hypothesize that fornix injury could be inducing hippocampus damage here.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…VBM studies have shown changes in the insula, orbitofrontal cortices, temporal lobes, thalamus, and cingulate cortex [ 35 ]. Using diffusion tensor and tractography, the hippocampus, fornix, and thalamus show significant difference from controls [ 36 , 37 ]. Functional MRIs studies highlighted alterations in hippocampal and amygdaloid regions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%